1989
DOI: 10.1111/j.1476-5381.1989.tb12622.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine‐induced inhibition of calcium channel current in cultured smooth muscle cells from pregnant rat myometrium

Abstract: 1 The inhibitory effect of caffeine on the calcium channel current was investigated in cultured myometrial cells isolated from pregnant rats. 2 Caffeine inhibited the calcium channel current elicited from a holding potential of -70 mV in a concentration-dependent manner. The IC50 was estimated to be 35 mm.3 The caffeine inhibition was not enhanced when calcium channels were opened by a conditioning depolarizing pulse sequence or when the number of inactivated calcium channels was increased at depolarized holdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…The similar inhibitory action of caffeine has been reported in rat aortic smooth muscle (Sato et al . , 1988) and in the cultured smooth muscle cells from the pregnant rat myometrium (Martin et al . , 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…The similar inhibitory action of caffeine has been reported in rat aortic smooth muscle (Sato et al . , 1988) and in the cultured smooth muscle cells from the pregnant rat myometrium (Martin et al . , 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, caffeine can inhibit plasmalemmal Ca L in cultured myometrial cells from pregnant rats (Martin et al, 1989). In these cells, caffeine inhibits the depolarizationinduced Ca 2ϩ current with an IC 50 value of 35 mM.…”
Section: Pharmacological Modulation Of Smooth Muscle Srmentioning
confidence: 99%
“…Caffeine, at specific concentration used, could induce inhibitory effect on smooth muscle contraction (Missiaen et al 1992). Moreover, Martin et al (1989) demonstrated that caffeine could inhibit voltage-dependent Ca2+ channel in cultured myometrial cells. The caffeine concentration used in our study could have been too low to ensure smooth muscle contraction since caffeine stimulate Ca-induced Ca release mechanism at concentration superior to 1 mM (Iino 1 990 b) .…”
Section: Discussionmentioning
confidence: 99%